BAHASA INDONESIA DAN NASIONALISME DI INDONESIA - Ni Nyoman Kertiasih (Universitas Warmadewa, 2018)
[Title: Indonesian Language and Nationalism in Indonesia] This paper reveals the relationship between the Indonesian language and nationalism, and their relation to one another. Indonesian recognized derived from the Malay language is the lingua franca formerly in trade in the archipelago. This paper is lifted language and nationalism with the following questions: (1) how the Malay language to be Indonesian? (2) how the spirit of Indonesian nationalism becomes a factor?, (3) how the Indonesian language in Indonesia's national and local context? From the results it appears that the Indonesian study originated from the ancient Malay language which evolved into the lingua franca in the association between the peoples of the Indonesian archipelago. Malay language that can momentum in youth congress Indonesia II (1928), expressed as the Indonesian language. Associated with nationalism, the Indonesian language becomes an important factor because of the language, ideas of nationhood developed within political organizations in the colonial period and the period afterwards. Indonesian in a local context to be understood that the regional languages have enriched the Indonesian language in its development. Next in the national context, the Indonesian language remain important, as a symbol of unity, a unifying tool, serves as an introduction in education, as a means of communication at the national level, as a means of development of culture, science, and technology.